The Influence of Transformational Leadership on Employee Performance in Public Organizations: A Case Study of the Regional Secretariat of Tangerang City - Yustikasari, Miranda; Hutauruk, Rosinta Paulina; Sa’adih, Sa’adih (Universitas Sang Bumi Ruwa Jurai, 2022)
This study investigates the influence of transformational leadership on employee performance within the Regional Secretariat of Tangerang City. Using a quantitative approach with survey data collected in 2021, this research examines how four dimensions of transformational leadership idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration affect task achievement and organizational citizenship behavior among civil servants. The results indicate that leadership behaviors that foster trust, inspiration, and employee development have a significant positive impact on performance outcomes. These findings offer practical insights for enhancing leadership practices in Indonesia’s urban public sector.